2012
DOI: 10.1016/j.gaitpost.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Functional near-infrared spectroscopy (fNIRS) of brain function during active balancing using a video game system

Abstract: Functional near-infrared spectroscopy (fNIRS) is a portable, non-invasive, brain imaging technology that uses low levels of non-ionizing light to record changes in cerebral blood flow in the brain through optical sensors placed on the surface of the scalp. These signals are recorded via flexible fiber optic cables, which allow neuroimaging experiments to be conducted on participants while performing tasks such as standing or walking. FNIRS has the potential to provide new insights into the evolution of brain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 33 publications
1
64
0
9
Order By: Relevance
“…51,52 Karim et al showed that playing exergames resulted in a robust hyperemic response in the superior temporal gryus and supramarginal gyrus, 51 indicating that these areas were important for balance. Furthermore, the duration of this response after cessation was prolonged (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) s longer than what would be expected), suggesting an adaptation of the vestibular network in response to the balance task.…”
Section: Participant's Experience Of Exergamingmentioning
confidence: 99%
“…51,52 Karim et al showed that playing exergames resulted in a robust hyperemic response in the superior temporal gryus and supramarginal gyrus, 51 indicating that these areas were important for balance. Furthermore, the duration of this response after cessation was prolonged (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) s longer than what would be expected), suggesting an adaptation of the vestibular network in response to the balance task.…”
Section: Participant's Experience Of Exergamingmentioning
confidence: 99%
“…5 Group mean changes in HbR responses for each task relative to rest. Error bars represent SD Brain Topogr studies remain inconsistent and analyses have focused primarily on HbO data (Cao et al 2015;Karim et al 2013;Karim et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Regardless of whether an FIR or canonical design matrix is assumed, the values of β (e.g., brain activity) can be estimated by the inversion of X in Eq. (6). The Gauss-Markov equation for the unbiased ordinary least squares (OLS) estimator is…”
Section: Theorymentioning
confidence: 99%
“…Because it is non-ionizing and non-confining, fNIRS is particularly well suited for non-invasive studies in children or infants. In addition, the portability of fNIRS and its ability to record brain signals during moderate subject movement has allowed its use during various tasks such as walking [3,4], balance [5][6][7], or social interaction [8], which otherwise could not be imaged by conventional fMRI.…”
Section: Introductionmentioning
confidence: 99%